The effects of food processing on biogenic amines formation - Chong, C. Y.; Abu Bakar, Fatimah; Abdul Rahman, Russly; Bakar, Jamilah; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Biological amines are nitrogenous compounds that occur naturally in wide variety of food. Histamine, putrescine, cadavarine, tyramine, spermine, spermidine, tryptamine and β-phenylethylamine are the biogenic amines that are normally present in foods. Although the biogenic amines play some important physiological functions but high level of amines can cause toxicological effects. High amount of amines can be produced by bacteria during amino acids decarboxylation and have been identified as one of the important agent causing seafood intoxication. Temperature is the major factor for controlling the biogenic amines formation in food. The effects of other alternatives are also discussed including salting, packaging, irradiation, high pressure processing and the use of starter culture. A variety of techniques can be combined together to control the microbial growth and enzyme activity during processing and storage for better shelf life extension and food safety.